Diet and The Risk of Endometriosis in Iranian Women: A Case-Control Study - Ashrafi, Mahnaz (Int J Fertil Steril, 2020)
BACKGROUND: Endometriosis is one of the most common pelvic diseases associated with dyspareunia, pelvic pain, and infertility. The primary aim of this study is to evaluate the role of diet on the risk of endometriosis among Iranian women. MATERIALS AND METHODS: This case-control study was conducted in two health research centres between 2015 and 2016. There were 207 women with endometriosis (case) and 206 women without endometriosis (control) who were evaluated by laparoscopy. The women were asked about their frequency of consumption per week of portions of se- lected dietary items in the Iranian diet in the year before the interview. RESULTS: The results indicated that intake of green vegetables (odds ratio [OR]=0.39, 95% confidence interval [CI]=0.21–0.74, Ptrend=0.004), red meat (OR=0.61, 95% CI=0.41–0.91, Ptrend=0.015) and dairy products (milk [OR=0.65, 95% CI=0.47–0.92, Ptrend=0.014], cheese [OR=0.53, 95% CI=0.37–0.76, Ptrend<0.001]), fresh fruit (OR=0.68, 95% CI=0.50–0.93, Ptrend=0.015) and grain legumes (OR=0.59, 95% CI=0.47–0.77; Ptrend<0.001) had a significant association with lower risk of endometriosis. Consumption of carrots, green tea, fish, eggs and oil was not significantly related to the risk of endometriosis. CONCLUSION: This study suggests that certain types of dietary components may be related to the risk of endometriosis.